Exploring the interplay of electron density distribution and electrostatic potential in the interaction of nilutamide and flutamide with androgen receptors using quantum crystallography - Balasubramanian, Hemalatha; Poomani, Kumaradhas; Kandasamy, Saravanan; Hathwar, Venkatesha R.; Gonnade, Rajesh G. (RSC Advances, 2026)
Prostate cancer is a malignant disease commonly found in men. Androgens support the growth and survival of prostate cancer cells. To control this growth and the spread of cancer cells, anti-androgen drugs are necessary to block androgen activity. Effective blocking of androgens depends mainly on the structure, intermolecular interactions and charge density distribution, electrostatic potential (ESP) and binding affinity of drug molecules. Nilutamide (NIL) and flutamide (FLU) are two structurally related non-steroidal anti-androgen drugs (NSAAs) which exhibit serious side effects. The present study explores the charge density distribution, electrostatic potential and intermolecular interactions of NIL and FLU determined from a high-resolution X-ray diffraction experiment and a solid-state quantum chemical theoretical study. Topological analysis of charge density reveals the electron density at the bond critical points of chemical bonds and intermolecular interactions. The electrostatic potential derived from the charge density distribution of both molecules in the crystal has been mapped, which allows a prediction of how the electrostatic interactions, hydrogen bonds, and van der Waals forces govern the binding of these two drug molecules with the androgen receptor at the electronic level. The ESP of interacting groups of both molecules in the androgen active site is approximated to the ESP of those groups in the crystals. The charge density distribution and the electrostatic potential of both molecules were compared. The difference in charge density is reflected in the ESP of NO2, CF3 and NH groups and the aromatic ring of both molecules, which is important for drug binding, metabolic stability and toxicity. A molecular docking simulation of both molecules with androgen receptors shows the difference in interactions and binding affinity in the binding pocket of the androgen receptor. The results of the high-resolution X-ray experiment and the advanced computational charge density study of NIL and FLU allows us to understand drug binding and is useful to relate their differing biological effects and toxicities at the electronic level. This information pertains to the design of a new potential androgen inhibitor with improved binding affinity and fewer side effects.